Konstruksi Makna Setara Melalui Perilaku Patriarkis Perempuan di Ruang Domestik dan Publik: Studi Kasus Kepada Anggota LSM Perempuan Di Yogyakarta - Miranti, Adita; Wibawa, Raja Satria (School of Communication - Atma Jaya Catholic University of Indonesia, 2021)
Gender basically discusses the meaning of equality between women and men in various aspects of life. The existence of men and women are two entities that are often distinguished in terms of sex and the roles that must be performed gender so that the potential to cause disparity. The purpose of this study is to analyze how the construction of the meaning of